Soviet relations with the Zionist entity during the October War 1973 (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Until now, the Zionist entity still holds the Soviet Union responsible for enabling the Syrians and Egyptians to launch the October war after providing them with advanced air defenses and helping them to establish ideological armies trained to use advanced weapons, while the Soviets assert that they only support peaceful solutions as a way to resolve the Arab-Israeli conflict, but the intervention of The United States of America, represented by the President of the National Security Council, Henry Kissinger, contributed to keeping the Soviets away from mediation efforts, so the United States was alone in this matter, with the approval of some Arab countries, despite its complete alignment with the Zionist entity, and thus the Soviets consider that the United States, with its support for the Zionist entity, forced the Arabs to choose a military solution to restore their land.